Replicating the CBOE VIX using a synthetic volatility index trading algorithm - Dayne Cary; Gary Van Vuuren (Cogent Economics & Finance, 2019)
This article tests whether a correlation exists between a stochastic synthetic volatility index (SVIX) and the Chicago Board Options Exchange (CBOE) volatility index (VIX) and assesses the success of the indicators' application by pairing an undeveloped trading strategy to gauge its forecasting accuracy. The SVIX aims to address the scaling limitations of the CBOE VIX. The SVIX allows traders to graph volatility as a 100% scale on securities that do not have an official CBOE VIX ticker symbol. The SVIX shows high correlation with the CBOE VIX. Backtesting indicators with an investment strategy using US stocks proved successful. The winning percentage of trades and net profit are positive only for long strategies and fail in short strategies.
Keywords: 330; volatility index; VIX; correlation; trading strategy